The contributions of the Wisconsin Special Olympics Program in the development of physical fitness and sport skill competencies for the mentally retarded population - Mixdorf, Cynthia D. (My University, 1980)
The focus of this study was to determine the effectiveness of the athletic preparation, in terms of physical fitness and sport skill competencies for the mentally retarded participants in Wisconsin Special Olympics (WSO). The specific problems were to identify the effectiveness of WSO athletic preparation, the qualifications of personnel involved in athletic preparation and the priority placed on athletic preparation by the State and Area levels. Standards were developed as a basis for meeting the criteria for each of the five hypotheses. Data was gathered through surveys of the WSO Coaches and Area Coordinators, a personal interview of the State Program Coordinator and a review of public financial documentation. The questionnaire responses were tabulated in terms of tally and percentages. Results of the study indicated that the athletic preparation provided through WSO does not meet the minimal standards related to necessary training time for the development of physical fitness and sport skill competencies. It was further identified that the majority of WSO Coaches do not meet the minimal standards established for effective coaching qualifications. In addition, available evidence does not indicate that WSO at the Area and State level regards athletic, preparation as a high priority within the total organization.